OPTIMASI PEMANFAATAN IRIGASI SUMUR POMPA (STUDI KASUS PADA SUMUR POMPA DI DESA WATULAWU KECAMATAN PONDIDAHA) - Erawan, Dedi (Jurnal Agroteknos, 2011)
ABSTRACTThe operation of groundwater irrigation requires additional cost for fuel and pump operators. This, therefore, require careful cost calculation in order to obtain expected income. For this purpose, the research was conducted to optimize the usage of irrigation water from one of wells at Watulawu, Pondidaha, to determine the most profitable crop species and cropping system. The optimization was conducted using a linier program with QSB (Quantitative System Business) software, with the objective function was the maximum profit of farming and the limiting function was the availability of irrigation water and planting size. Out of optimized crop species (rice, maize, groundnut, and soybean), groundnut and rice were the profitable crops. Planting size for both species was varied during each planting season, depending on crop water requirement and rainfall. Early cropping on March required less irrigation water than early cropping on February Keywords : Groundwater irrigation, QBS Software